A Qualitative Study on the Conceptualisation of Mental Health Amongst South Korean Migrants to Australia - Annemarie Klingenberg; Sunjoo Heo; Jaklin Eliott (Psychotherapy and Counselling Journal of Australia)
An increase in global awareness of the mental health needs of migrant communities, and recognition of the underutilisation of support services by these communities, has prompted calls for culturally appropriate and competent interventions to address their needs. Providing such culturally effective treatment and mental health services, particularly for culturally and linguistically diverse (CALD) subgroups, requires understanding their perspectives on mental health. This research was led by a migrant from South Korea, living, studying, and working in Australia, and explored how South Korean migrants to Australia talk about mental health and what they need to support their mental health. A qualitative study was conducted via telephone or online web-conferencing using semi-structured interviews. A critical realist approach facilitated consideration and understanding of themes addressing participant perspectives of what promoted South Korean migrants’ mental health in the Australian context. All interviews were thematically analysed, and three major themes centred around (shifting) cultural norms were identified. These were increasing individualism (e.g., through self-discovery); the expression of individually new-found norms; and issues around belonging in society. The purpose of this article is to translate these findings into counselling practice and community initiatives to provide practitioners with greater insights into concepts this population group has identified as impacting their mental health.